1992
DOI: 10.1002/1097-0142(19920515)69:10<2484::aid-cncr2820691017>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic findings in liposarcoma correlate with histopathologic subtypes

Abstract: The cytogenetic findings in 31 liposarcomas from 26 patients are reported. Four other tumors did not grow. Three histologic types are represented in this analysis. The well‐differentiated liposarcomas were characterized by telomeric associations, large marker chromosomes and ring chromosomes, and in some cases, double minutes. The pleomorphic liposarcomas contained very high clonal chromosomal numbers with near‐tetraploid modes and numerous variable, often unidentifiable, chromosomal abnormalities. The myxoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 24 publications
3
57
1
Order By: Relevance
“…In contrast to the highly complex and inconsistent karyotypes obtained by chromosomal banding analysis 6,13 and to one recurrent chromosomal abnormality detected with CGH in a small number of pleomorphic LS analyzed by Parente et al, 22 we identified in our series of pleomorphic LS analyzed by CGH a considerable number of recurrent chromosomal imbalances. Moreover, our data show that the DNA copy number changes detected in pleomorphic LS differ essentially from those in the cytomorphologically similar high-grade areas of dedifferentiated LS and from those in well-differentiated LS/ALT described in the literature.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In contrast to the highly complex and inconsistent karyotypes obtained by chromosomal banding analysis 6,13 and to one recurrent chromosomal abnormality detected with CGH in a small number of pleomorphic LS analyzed by Parente et al, 22 we identified in our series of pleomorphic LS analyzed by CGH a considerable number of recurrent chromosomal imbalances. Moreover, our data show that the DNA copy number changes detected in pleomorphic LS differ essentially from those in the cytomorphologically similar high-grade areas of dedifferentiated LS and from those in well-differentiated LS/ALT described in the literature.…”
Section: Discussioncontrasting
confidence: 92%
“…[5][6][7][8] FISH studies have shown that the rings and giant marker chromosomes of welldifferentiated LS/ALT are composed, exclusively or partly, of amplified material from chromosomal subregion 12q13-15. 7 An additional subset of well-differentiated LS/ALT have duplications of 12q15-q24.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myxoid liposarcomas are characterized by a unique chromosomal translocation, t(12;16) (q13;p11), resulting in a fusion of the DDIT3 gene (also known as CHOP or GADD153) on chromosome 12 and the FUS gene (also referred to as TSL) on chromosome 16. [35][36][37] A molecular analysis to find the TSL-CHOP translocation will be of help in establishing a definitive diagnosis. 38 Adequate material for molecular analysis was available only in one of our cases of well-differentiated liposarcoma with myxoid stroma (case 2); amplification for MDM2 was demonstrated by FISH but the DDIT3 translocation was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…Myxoid liposarcoma is a soft tissue sarcoma which is characterised by a reciprocal translocation of chromosomes 12 and 16, t(12;16)(q13;pll), in 9070 of cases (52)(53)(54). The remarkable histotype specificity of this aberration as depicted by its incidence and the lack of such a translocation in any other subtype of liposarcoma or myxoid sarcoma places it amongst the more important diagnostic markers in soft tissue sarcomas.…”
Section: Liposarcomamentioning
confidence: 99%